Workplace transitions: the role of social media and boundary management - Hecht, Emeline, author; Williams, Elizabeth, advisor; Faw, Meara, committee member; Long, Ziyu, committee member; Humphrey, Michael, committee member (Colorado State University. Libraries, 2023)
Previous literature has examined the workplace transition and its implications for the organization and its members. However, minimal studies have been conducted on how social media may influence the increasingly common occurrence of workplace transitions. This study explores the boundaries that individuals create and negotiate when using social media in the process of organizational transitions. Through twenty-five interviews with individuals who recently changed workplaces, this project highlights experiences of social media boundary management practices as participants navigated their assimilation to and from workplaces. This research project asked what strategies of boundary management employees utilize on social media across multiple assimilation phases. Eight boundary management strategies emerged from the data. The findings of this study expand knowledge of the assimilation process during a job transition and how privacy is managed during the multiple phases, providing insight into the implications of rule violations on organizational membership and the way that privacy rules are communicated between organizational members.
Keywords: communication privacy; workplace transitions; social media; boundary management